Profiling inclusive primary school teachers: With focus on transforming teacher-training processes at public educational institutions in the district of cartagena, colombia (2021)
The main objective of this study is to profile inclusive primary school teachers at educational institutions in the District of Cartagena, Colombia. The sample consists of 91 teachers from six public primary schools. This is a mixed design study supported by both quantitative and qualitative approaches. An ad hoc questionnaire is used to survey teachers and an orientation questionnaire guide is used to survey focus groups of teachers and professionals that support students with disabilities or with exceptional talents. The results show that the new profile of inclusive teachers includes training and competency variables and the following disciplinary learning approaches: Pedagogical-didactic, psych-pedagogical, neuro-psych pedagogical, and psychiatry. It is concluded that inclusive teachers transform training processes through knowledge applied to particular situations with their students, which is accompanied by humanistic and coexistence skills. This guarantees the placement of students with and without disabilities in a regular classroom, without inferring their academic performances, and guarantees the generation of social benefits for all students.